Pengembangan Media Pembelajaran Flipbook Maker pada Pemangkasan Increase Layer Vertikal Mahasiswa Tata Rias dan Kecantikan - Putri, Rada; Saputra, Indra (TSAQOFAH, 2025)
This study is motivated by the development of the Industrial Revolution 4.0 era, marked by advances in technology, information, and communication that have brought significant changes to lifestyle, social, economic, and cultural patterns. One relevant educational innovation is the use of digital learning media based on interactive e-modules, such as Flipbook Maker. The research aims to produce a Flipbook Maker learning medium that is valid and practical for teaching vertical increase layer haircutting to students of the Beauty and Cosmetology Department at Universitas Negeri Padang. This research employed a Research and Development (R&D) method with the 4D development model (Define, Design, Development, Dissemination). The instruments used were validity and practicality questionnaires, completed by lecturers and students to assess the feasibility of the medium. The results show material expert validity of 0.67 (valid), media expert validity of 0.87 (highly valid), and language expert validity of 0.85 (highly valid). The practicality score from students reached 0.91 (highly practical). In conclusion, the Flipbook Maker medium for teaching vertical increase layer haircutting meets the criteria of validity and practicality, making it suitable as an interactive teaching material to support the learning process in the digital era.